Tait, Robert H. The Robert H. Tait Fonds - Tait, Robert , 1891-1964; Riggs, Bertram G., 1954- (Memorial University of Newfoundland. Libraries, 1919)
Robert H. Tait had a lengthy career as a soldier, lawyer, civil servant, writer and lecturer. The collection consists of a typescript written by Tait on Newfoundland's role in pioneer transAtlantic aviation between 1919 and 1937, recording each of the attempts to cross the Atlantic using Newfoundland or Labrador as a starting, ending, or stop-over point. There are 73 photographs depicting the planes and the people involved in these flights. Includes a map and a chart detailing the successful flights and the attempts, and as well as correspondence between Tait and Sir Arthur Whitten Brown (of Alcock and Brown fame).